New precipitating factors for migraine during Covid-19 pandemic lockdown - Al-Hashel, Jasem Youssef; Abokalawa, Fathi; Ahmed, Samar Farouk (Headache Medicine, 2022)
Background: Lock down caused sudden lifestyle changes and represented a massive impact on human health. We aimed to report new migraine headache precipitating factors due to lifestyle changes during coronavirus disease 2019 (COVID-19) Pandemic lockdown. Methods: This cross-sectional survey included patients diagnosed with migraine based on The International Classification of Headache Disorders, 3rd edition (ICDH-3). During the lockdown, we submitted an online self-reported web-based questionnaire to patients already diagnosed with migraine and attending headache clinic at Ibn Sian Hospital in Kuwait. Questions explored different new precipitating factors of migraine headache attacks during COVID-19 pandemic lockdown compared to precipitating factors before lockdown. Results: A total of 340 migraine patients responded to online questionnaire. The mean age of them is 34.65 years. Females were predominant 79.1%. Majority of the cohort 85 % has more than one trigger of migraine headache attack. During pandemic, the common precipitating factors were smell of strong odors in 214 (62.9%), followed by certain food in 175 (51.8%), sleep disturbance in 120 (35.3%), emotional or mental stress in 80 (23.6%), caffeine in 80 (23.6%), flickers of light in 78 (22.9%), weather changes in 68(20%), smoking in 65 (19.12%), noise in 56 (16.5%), sun light exposure in 41 (12.1%), fasting/ hypoglycemia in 40 (11.7%), hormonal changes in 37 (10.6%), physical excretion/fatigue in 24 (7.1%), screen exposure in 20 (5.9%), and dehydration in 14 (4.1%) patients. Before pandemic, noises 200 (58.8%), flicker of light 180 (52.9%), weather changes 175 (51.5%), sun light 170 (50%), food 160 (48.5%) and 130 (38.2%) sleep deprivation were the most common precipitating factors of migraine. 40% did not report precipitating factors for migraine before lockdown. Conclusions: Change of habits during lock down exposed migraine patients to different precipitating factors. Strong odors, food, sleep disturbance and stress were the most common migraine headache precipitating factors during COVID-19 lockdown.